Utilisation des déchets de biscuiterie dans l'alimentation de la daurade Sparus aurata - BRINI, Béchir; AYARI, A. (INSTM Bulletin : Marine and Freshwater Sciences, 1996)
An experience is carried during 84 days on Sea-bream 10 g initial mean weight. The purpose is to reduce cost by decreasing protein level and increasing carbohydrate. It consist to introduce, in food, a raw material (scraps cracker) locally available and rich in carbohydrate, to substitute so another one (Soya) which is imported and contain more protein. Results showed that food containing 16 % of scraps cracker can give same growth, survival and food conversion than another containing 16 % of soya. This is possible if scraps cracker is highly cooked. Unless, results are less performance. This experimental food, rich in carbohydrate, has a low cost and good cohesion which limit food loss. However, these comforting results need confirmation by different scraps cracker incorporation levels in food and at different protein rates.